Gun violence as a public health issue: Media advocacy, framing and implications for communication. (June 2022) - McKeever, Brooke W.; Choi, Minhee; Walker, Denetra; McKeever, Robert
Following a recent push to reframe gun violence as a public health issue, an online survey (N = 510) helped explore frame salience and frame adoption through the lens of media advocacy. Findings revealed that gun control and gun rights frames are salient, and television, social media and newspapers are the most popular sources of gun violence information. Individuals are being held responsible, while background checks were the most salient and adopted solution among Americans. Three gun rights organizations were the most salient organizations from media coverage related to gun violence. Theoretical and practical implications are discussed.